The Make Sweet Potato Chips with Different Flavor by Women Group Farmers Harapan Baru in Walelagama District, Jayawijaya, Papua - Ekalia Yusiana (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2018)
Sweet potatoes are a cultural plant for the people of the Pegunungan Tengah, Papua because every day people in this region are always use sweet potatoes. Pegunungan Tengah, Papua community knows sweet potatoes with the name hipere. The purpose of this service is to change the behavior patterns of farmers in the process of processing sweet potatoes that have never been processed into regional superior products in Pegunungan Tengah, Papua. The implementation of this activity through KKN-PPM is by providing socialization and training in making various flavors of sweet potato chips. The results of this community service are the people of Wamena District can make various kinds of flavored sweet potato chips food products, thus helping the community in creating added value of products and can increase family income.